A design for pre-service seminar on the use of the UP-SEC elementary science guides - Araneta, Lydia D. (1972)
The purpose of this study was to design a preservice seminar on the use of the UP-SEC Elementary Science Guides for prospective student teachers in the Laboratory School of Zamboanga State College. A set of interview questions was prepared for each group of respondents. The data from each set of interview and the analysis of the science background of prospective student teachers revealed the following problems: unfamiliarity with the content of the UP-SEC Elementary Science Grades, inadequate knowledge of the content, lack of manipulative skills, difficulty in understanding directions, limited supply of science equipment, difficulty in securing materials, limited time to carry out some of the more complex activities, and inability to cope with unexpected situations.
"December, 1972."
Thesis (M.A.T. : Elementary Science)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Zamboanga City (Zamboanga del Sur).; Student teachers -- Philippines -- Zamboanga City (Zamboanga del Sur).